Repeated Cell Therapy:A Paradigm Shift Whose Time Has Come - Bolli, Roberto (Circ Res, 2017)
Although treatment with stem/progenitor cells is a promising approach to heart disease, enthusiasm for cell therapy has been dampened by the inconsistent, modest, borderline, or undetectable benefits reported in clinical trials (all of which have used one dose of cells)(1,2,3,4). As a result, clinical translation has not occurred (no cell-based therapy is close to being approved for heart disease), and a rising tide of skepticism has bedeviled the field,(5, 6) leading some critics even to question whether clinical studies should continue. Here I propose that a major reason for the modest, borderline, or disappointing results is the administration of only one dose of cells, which causes the benefits of cell therapy to be underestimated. Iargue that just as most pharmacologic agents are ineffective when given once but can be highly effective when given repeatedly, so a cell product may be ineffective, or modestly effective, when given as a single treatment, but may turn out to be quite efficacious if given repeatedly. This concept constitutes a major paradigm shift, with potentially vast implications for the entire field of reparative medicine.